Mortuary House - Unknown (1915)
A frontal pole was erected in front of the gable-roofed structure, and was later purchased by C.F. Newcombe for the American Museum of Natural History in New York. At the top of the pole is the killer whale, which is symbolic of people who have drowned, and below, the supernatural snag, which was credited with the power to upset canoes.